To Assess the Perception of rural population of Julkey Village about their own general, physical, mental and emotional health - Muhammad Waqar, Minahil Fatima, Zoya Moazzam, Muhammad Sami Masood, Fatima Zia, Kanz-Ul Iman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Perception about different aspects of health including general, physical, mental and emotional health plays a pivotal role in implementation of more efficient health service provision. The rural population of Pakistan has low literacy rate which is one of the major predisposing factors of decreased health awareness among them. Methods: A cross-sectional study based on verified sf-36 questionnaire for the measurement of general, physical, mental and emotional health status among rural population was conducted during December 2021 till May 2022 in Julkey village, Lahore. Results: A total of 256 individuals participated in our study with 163 males and 93 females having mean age of 36.95±12.81 SD (in years). The sample consisted of 30% from age group 15-30, 65% from age group 31-60 and 4% from 61+ age group. While inquiring about general health 57.1% males and 49.5% females defined their health as excellent. Limitation of physical activities in females was more than males. Emotional health of males was better than females and majority of the participants considered themselves as a happy person. Only 1.8% males and 5.6% females think they feel tired all of the time. Interestingly, strong association of general health and limitation of activities with age was seen with p value of 0.00. Conclusion: A large proportion of sample had a good perception about their health. However, creating more health issues awareness and better health care facilities can improve the situation further. Keywords: Rural Population, Physical and Mental Health, Emotional Health, General Health